Sinergi Hukum Adat dan Hukum Islam dalam Penyelesaian Sengketa Tanah Adat : Studi Kasus Desa Adat Pampang, Samarinda - Iriantoro, Agung; Sujatmiko, Sujatmiko (STAINI Press, 2025)
This study aims to analyze the synergy between customary law and Islamic law in the mechanism for resolving customary land disputes in Pampang Customary Village, North Samarinda. The problem of customary land in this region is not only related to the aspect of ownership, but also touches the social, spiritual, and cultural dimensions of the Dayak Kenyah community. The research approach uses qualitative methods with a combination of normative and empirical approaches, through the analysis of legal documents, interviews with traditional leaders, and observation of customary mediation practices. The results of the study show that dispute resolution in Pampang Village is carried out through a consensus deliberation mechanism led by the Customary Head, with an emphasis on the value of justice, social balance, and community peace. This mechanism has a substantive conformity with the principle of ṣulḥ (peace) in Islamic law, which emphasizes peaceful, participatory, and equitable resolution of disputes. The research discussion emphasized that the integration between customary law and Islamic law can strengthen social legitimacy, increase legal certainty, and present a more contextual dispute resolution model for customary law communities. These findings have implications for the need for state recognition of customary decisions as part of a pluralistic and equitable national legal system.